Satellite Image Contrast Enhancement Using Discrete Wavelet Transform and Singular Value Decomposition - Demirel, Hasan; Ozcinar, Cagri; Anbarjafari, Gholamreza (IEEE-Inst Electrical Electronics Engineers Inc, 2010)
In this letter, a new satellite image contrast enhancement technique based on the discrete wavelet transform (DWT) and singular value decomposition has been proposed. The technique decomposes the input image into the four frequency subbands by using DWT and estimates the singular value matrix of the low-low subband image, and, then, it reconstructs the enhanced image by applying inverse DWT. The technique is compared with conventional image equalization techniques such as standard general histogram equalization and local histogram equalization, as well as state-of-the-art techniques such as brightness preserving dynamic histogram equalization and singular value equalization. The experimental results show the superiority of the proposed method over conventional and state-of-the-art techniques.
Keywords: Discrete wavelet transform; image equalization; satellite image contrast enhancement